A Tale of Two Journals: Women's Representation in Public Administration Scholarship. (2nd January 2019) - Scutelnicu, Gina; Knepper, Hillary J.
Abstract : This study examines women's representation in public administration scholarship by analyzing the research method and the content of 618 articles published in the Journal of Public Administration Research and Theory, and the Public Performance and Management Review from 2004 to 2013. Findings indicate that women publish less than men as solo, lead, and top 10 authors in these two journals. The study identifies men's publishing acceptance of articles using predominantly quantitative methods and women's publishing acceptance of articles using predominantly qualitative methods. Finally, this study finds that university affiliation may contribute to publishing in one or the other journal under research. This study is suggestive in nature and provides further evidence of the underrepresentation of women in public administration scholarship.